The influence mechanism of service innovation on consumer mobile sharing in the age of digital intelligence - Peng, Hongxia; Xu, Shuwei; Yang, Mei (Frontiers in Communication, 2023)
Introduction Digitalization is moving closer to traditional service companies. Consumers have new behavioral characteristics, and operators need to adopt new marketing strategies. Methods We used CiteSpace software to analyze the literature related to customer delight in CNKI and Web of Science databases. We constructed models and research hypotheses based on theoretical studies related to customer delight and mobile sharing. The data were collected through questionnaires and the article used structural equation modeling and regression analysis to test the mediating role of customer delight and the moderating role of individual innovativeness in the theoretical model. Results Among the four dimensions of service innovation, only interface innovation and delivery innovation, affect consumers' mobile sharing through customer delight, and customer delight has a very significant positive impact on mobile sharing. The mediating effect of customer delight is affected by the individual innovation of consumers in the path of delivering innovation. Discussion In the future, catering and takeaway companies can innovate the delivery process of product information to reach consumers, and provide a personalized interface to accurately meet the different needs of customers.